1983
DOI: 10.1016/s0735-1097(83)80332-5
|View full text |Cite
|
Sign up to set email alerts
|

Poor R wave progression in the precordial leads: Clinical implications for the diagnosis of myocardial infarction

Abstract: A definite diagnosis of anterior myocardial infarction is often difficult to make in patients when a pattern of poor R wave progression in the precordial leads is present on the electrocardiogram. The purpose of this study was to determine whether a mathematical model could be devised to identify patients with anterior infarction among 102 consecutive patients with poor R wave progression. Each patient underwent exercise testing with thallium scanning. The diagnosis of anterior infarction was established in 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…The sum of R-wave in lead V1 to V6 was measured in each patient. PRWP was defined as RV3 ≤ 3 mm according to the DePace criteria [3].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sum of R-wave in lead V1 to V6 was measured in each patient. PRWP was defined as RV3 ≤ 3 mm according to the DePace criteria [3].…”
Section: Methodsmentioning
confidence: 99%
“…The role of 12-lead electrocardiogram (ECG) in diagnosing myocardial infarction (MI) is well established [1], and poor R-wave progression (PRWP) is interpreted as the probable anterior MI [2], [3]. However, regeneration of R-wave or disappearance of Q-wave sometimes occurs after MI especially in the coronary intervention era [4], [5], [6], [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies have shown that after revascularization in patients with acute myocardial infarction, R wave amplitude in ECG increased [19], [20]. Patients with small or absent initial R waves in the anterior chest leads, resulting in QS complexes or “poor R wave progression,” could also be diagnosed as myocardial infarction [21]–[23].…”
Section: Introductionmentioning
confidence: 99%
“…This is the first study to investigate this topic and suggest a reasonable cause of PRWP, i.e., a low cardiothoracic ratio. The prevalence of PRWP in the general population (0.5% by the Marquette criterion or 1.8% by the simple criterion based on R-wave amplitude of only two precordial leads) was even lower than in hospitalized adult patients (10%) or in patients examined for CAD (8%) 2)8). Subjects with PRWP tend to be female, younger, weigh less, and shorter in height than those without PRWP.…”
Section: Discussionmentioning
confidence: 86%